Pengaruh Kualitas Produk Dan Potongan Harga Terhadap Minat Beli Produk Wuling - Sugi Andrian Sukmana; Mashadi Mashadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this study was to determine how much influence the Product Quality and Price Discounts on Interest in Buying Wuling Products. The data of this study were obtained from a questionnaire distributed to prospective consumers who have an interest in buying Wuling products, marked by a walk-in at Wuling Bogor dealerships from March 1, 2020 to May 31, 2020 with a total of 65 respondents treated. This research uses quantitative research methods with multiple linear analysis methods as a hypothesis testing tool. The results of this study indicate that the Product Quality variable has no influence on the Wuling Product Purchase Interest. Discounts have an influence on interest in buying Wuling products Keywords: customer satisfaction, consumer behavior, marketing mix